Active Learning Methodologies and Educational Ethics (Docentes 2.0 Journal, 2022)
The role of active learning methodologies focuses on promoting the integral and dynamic participation of the student in his educational process instead of being only a recipient of knowledge. This essay aims to highlight the fundamental role played by active learning methodologies, where the educational process focuses on promoting the comprehensive and dynamic participation of the student rather than just being a recipient of knowledge. This essay was established under the deductive method, in the hermeneutical paradigm, with a qualitative approach of an interpretive type and topical narrative design. Likewise, the two main ethical problems that arise in academia and research are unfolded: plagiarism and conflict of interest in peer review, where the said problem is aggravated when it comes to hiring or granting promotions because, on numerous occasions, the contracts or incentives are obtained by the number of articles published or based on the citations obtained by the authors in peer-reviewed and indexed journals with a high impact factor, being able to present the case of favoring fellow students or friends in peer review. Without forgetting that the National System of Researchers (SNI) grants its members extra monthly incentives ranging from 7 thousand to 33 thousand pesos (level III researcher).
Keywords: Active learning; active method of learning; active method; teacher ethics